1990
DOI: 10.1155/1990/60495
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Symptomatic Non‐ParasiticLiver Cysts–Surgical Treatment VersusAlcohol Injection Therapy

Abstract: Fourteen patients with benign symptomatic non-parasitic cysts of the liver were either surgically treated, had alcohol injected into the cysts, underwent deroofing of the cyst or in 5, a cystectomy was done. Alcohol was injected into 6 patients and there has been no recurrence for as long as 5 years and 8 months after the treatment. Liver dysfunction occurred in 3 patients given blood transfusion during the surgery and/or postoperative course, an elevated temperature (over 39C) occurred in one patient. Adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…A congenital origin is supported by the occurrence of the cysts in fetuses and newborns, 636 by a case presenting as a congenital diaphragmatic hernia, 644 and the association of another case with the Peutz-Jeghers syndrome. 645 In the past, the treatment of choice of solitary cysts was excision, 646 but this has been supplanted by aspiration and sclerotherapy, 647,648 or laparoscopic fenestration. 649,650…”
Section: Solitary (Non-parasitic) Bile Duct Cystmentioning
confidence: 99%
“…A congenital origin is supported by the occurrence of the cysts in fetuses and newborns, 636 by a case presenting as a congenital diaphragmatic hernia, 644 and the association of another case with the Peutz-Jeghers syndrome. 645 In the past, the treatment of choice of solitary cysts was excision, 646 but this has been supplanted by aspiration and sclerotherapy, 647,648 or laparoscopic fenestration. 649,650…”
Section: Solitary (Non-parasitic) Bile Duct Cystmentioning
confidence: 99%
“…The etiology, physiology, anatomy, occurrence, and surgical treatment of liver cysts have been outlined by other authors [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. Aspiration of cystic fluid without sclerotherapy does not result in a permanent reduction of volume, and the relief of symptoms is only temporary [17]; however, during the past two decades several authors have reported on satisfactory results of ethanol sclerotherapy replacing surgery as the method of choice in solitary symptomatic cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nonsurgical methods, percuta neous needle aspiration, under ultrasound or computed tomography guidance, and alcohol sclerotherapy are gain ing favor because they are effective, technically simple, minimally invasive and probably feasible on an outpa tient basis [18][19][20], Malignant degeneration, a coagulative defect of the patient, and communication of the cyst with the biliary tree are contraindications. However, one should not minimize the risks of this method, such as hemorrhage, sepsis, bile loss into the peritoneal cavity and the high percentage of recurrences [21][22][23].…”
Section: Discussionmentioning
confidence: 99%